To Corrode Prison Cisnormativity: the Artetransformando: LGBTQI+ Encarceradxs project (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article presents a report of the creative living together at the Evaristo de Moraes Penitentiary, in Rio de Janeiro, with a group of sexual dissident and disobedient people. With emphasis on trans experiences in prison, this text exposes the smuggling tactics - since the cultivation of beauty, sensitivity and art - that aim to problematize the penal institution as a territory of radicalization of cisnormative violence.
Keywords: Gender; Prison; Cisnormativity; Drama; Transgenders